2009
DOI: 10.1002/asi.21032
|View full text |Cite
|
Sign up to set email alerts
|

An exploration into the practices of library Web usability in ARL academic libraries

Abstract: A survey of the 113 academic libraries of the Association of Research Libraries (ARL) was administered to investigate whether Web usability Policies/Standards/ Guidelines (PSGs) are in place, the levels of difficulty surrounding implementation, the impact of PSGs on actual usability practice, e.g., testing, resources, etc., and the relationship between ARL ranking and usability practice or PSGs. The response rate was over 74%. Results show that 25 (30%) libraries have PSGs dedicated to Web usability. Seventy-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Research shows that supervisors' lack of knowledge about websites inhibits user-centered website design. 17 A respondent from Chen et al's study reports, "It's really a pain trying to connect with our administration on the topic of Web design and usability, because even definitions are completely out the window" and "the dean and the associate directors know little about the need for usability and view it as a last minute check-off, so they can say that the Web site is tested and usable." 18 Lack of supervisor support inhibits website usability.…”
Section: Institutional Forcesmentioning
confidence: 99%
See 3 more Smart Citations
“…Research shows that supervisors' lack of knowledge about websites inhibits user-centered website design. 17 A respondent from Chen et al's study reports, "It's really a pain trying to connect with our administration on the topic of Web design and usability, because even definitions are completely out the window" and "the dean and the associate directors know little about the need for usability and view it as a last minute check-off, so they can say that the Web site is tested and usable." 18 Lack of supervisor support inhibits website usability.…”
Section: Institutional Forcesmentioning
confidence: 99%
“…Identified secondary sources are consultations with experts, other divisions within the library, webmasters, web committees, and focus groups. 20 The most widely used method is consultation with experts. 21 Experts uncover technical flaws and any obvious usability problems with a design, 22 facilitate focus groups, 23 and create new information architecture.…”
Section: Institutional Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a survey of the 113 ARL libraries with a 74 percent response rate, Chen, Germane, and Yang found that 85 percent performed usability testing on some aspect of their website. 6 Ward and Hiller note that, in the past decade, "usability testing has become an integral component of Web design and development in libraries." 7 Defined in a number of ways, usability testing is generally used to assess the design effectiveness of an interface.…”
Section: Review Of the Literaturementioning
confidence: 99%